Empowering the Younger Generation: Building Healthy Living Behaviors and Brand Awareness of Multivitamins - Nuradina, Kartika; Aziz, Dadan Abdul; Wiryani, Detya; Syarif, Devyanthi; Jaya, Rama Chandra; Sofiati, Nunung Ayu; Kamal, Muhhammad Ikhsan; Ekapaula, Rolla (International Journal of Community Service & Engagement, 2025)
Healthy living behavior has emerged as a critical issue that warrants promotion across all segments of society, particularly among the younger generation, who are regarded as vital national assets. The current generation exhibits lifestyle changes characterized by emerging trends, an abundance of fast food, unbalanced nutrition, high stress levels, and insufficient physical activity. These factors pose significant risks to their overall health. The interventions conducted in this study aim to cultivate awareness of both physical and psychological needs that support a healthy and prosperous life. They also encourage the recognition of the importance of nutrition and the availability of multivitamin brands in the market, facilitate intrapersonal communication for better self-understanding, and promote financial management to adopt and maintain a healthy lifestyle. The results of this community service program indicate a notable shift in the younger generation’s mindset toward greater openness and acceptance of healthy living. They are more motivated to practice healthy behaviors, and their awareness of multivitamin products has increased significantly. This awareness positions multivitamins as essential nutrients to support bodily needs and as a long-term investment in health